2021
DOI: 10.3389/fpsyt.2021.691327
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Instagram Data to Identify Usage Patterns Associated With Schizophrenia Spectrum Disorders

Abstract: Background and Objectives: Prior research has successfully identified linguistic and behavioral patterns associated with schizophrenia spectrum disorders (SSD) from user generated social media activity. Few studies, however, have explored the potential for image analysis to inform psychiatric care for individuals with SSD. Given the popularity of image-based platforms, such as Instagram, investigating user generated image data could further strengthen associations between social media activity and behavioral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“… 171 Models applied to Facebook and other social platforms (e.g., Twitter and Reddit) have been successful in predicting the diagnosis of psychosis, anorexia, anxiety, and stress levels. 196 , 217 , 218 In addition to the language analysis for the user posts and comments, ML models may also process media data such as Instagram images 219 or integrate images and text to infer the user’s mental state. 219 , 220 Entries of online search also form a complementary and equally compelling dataset alongside social media activity.…”
Section: Ml-powered Technologies For Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“… 171 Models applied to Facebook and other social platforms (e.g., Twitter and Reddit) have been successful in predicting the diagnosis of psychosis, anorexia, anxiety, and stress levels. 196 , 217 , 218 In addition to the language analysis for the user posts and comments, ML models may also process media data such as Instagram images 219 or integrate images and text to infer the user’s mental state. 219 , 220 Entries of online search also form a complementary and equally compelling dataset alongside social media activity.…”
Section: Ml-powered Technologies For Psychiatrymentioning
confidence: 99%
“… 196 , 217 , 218 In addition to the language analysis for the user posts and comments, ML models may also process media data such as Instagram images 219 or integrate images and text to infer the user’s mental state. 219 , 220 Entries of online search also form a complementary and equally compelling dataset alongside social media activity.…”
Section: Ml-powered Technologies For Psychiatrymentioning
confidence: 99%
“…In addition to the linguistic features of social media posts, the clinical utility of visual content on Instagram has also been explored. Hänsel et al [ 11 ] extracted image features such as color composition and the number of faces depicted from nearly 12000 Instagram posts from 68 individuals with schizophrenia spectrum disorders and 34 healthy controls. The study found that users with schizophrenia posted images with significantly lower saturation, colorfulness, and number of faces.…”
Section: Social Mediamentioning
confidence: 99%
“…Note that all features were computed at the individual participant level. More details about this process can be found in Multimedia Appendix 1 [7,12,14,[24][25][26][27][28][29].…”
Section: Feature Engineeringmentioning
confidence: 99%